Licoricidin combats gastric cancer by targeting the ICMT/Ras pathway in vitro and in vivo - Ma, Hanwei; Wu, Fahong; Bai, Yinliang; Wang, Tianwei; Ma, Shangxian; Guo, Liuqing; Liu, Guiyuan; Leng, Guangxian; Kong, Yin; Zhang, Youcheng (Frontiers in Pharmacology, 2022)
Licoricidin, a type of isoflavonoid extracted from the root of Glycyrrhiza glabra, has been widely proven to possess multiple biological activities, including anti-cancer effects as well as a powerful antimicrobial effect against Helicobacter pylori (H. pylori). However, the exact mechanism of Licoricidin against gastric cancer remains unclear. In this paper, we comprehensively studied the effects of Licoricidin on MGC-803 gastric cancer cells in vitro and in vivo, and further explored its mechanism of the action. The results revealed that Licoricidin exhibited multiple anti-gastric cancer activities, including suppressing proliferation, inducing apoptosis, arresting the cell cycle in G0/G1 phase, inhibiting migration and invasion abilities of MGC-803 gastric cancer cells. Besides this, a total of 5861 proteins were identified by quantitative proteomics research strategy of TMT labeling, of which 19 differential proteins (2 up-regulated and 17 down-regulated) were screened out. Combining bioinformatics analyses and the reported roles in cancer progression of the 19 proteins, we speculated that isoprenyl carboxyl methyltransferase (ICMT) was the most likely target of Licoricidin. Western blot assays and IHC assays subsequently proved that Licoricidin significantly down-regulated the expression of ICMT, both in MGC-803 cells and xenograft tumors. Moreover, Licoricidin effectively reduced the level of active Ras-GTP and blocked the phosphorylation of Raf and Erk, which may be involved in the anti-gastric cancer effects of Licoricidin. In summary, we first demonstrated that Licoricidin exerted favourable anti-gastric cancer activities via the ICMT/Ras pathway, suggesting that Licoricidin, as a natural product, could be a novel candidate for the management of gastric cancer.